The relationship between perceived classroom climate and academic performance among English-major teacher education students in Guangxi, China: The mediating role of student engagement - Ma, Yan; Wei, Changwu (Frontiers in Psychology, 2022)
The academic performance of teacher education students predicts their future career development and it is also a significant factor related to their future students’ academic performance. However, little is known about the associations between perceived classroom climate, student engagement and academic performance, especially for English-major teacher education students. This study was to examine English-major teacher education students’ academic performance in relation to perceived classroom climate, student engagement. The questionnaire consisted of the Emotional Classroom Climate Scale, the Utrecht Work Engagement Scale – Student Form-3 Item (UWES-SF-3), and the 5-item Academic Performance Scale. This study investigated 307 English-major teacher education students in Guangxi, China. Among them, 280 (91.2%) were females, and 27 (8.8%) were males, aged between 18 and 24 (M = 20.34, SD = 1.26). Results indicated that perceived classroom climate was positively associated with student engagement and academic performance among English-major teacher education students; their student engagement was positively associated with their academic performance, and student engagement partially mediated the relationship between perceived classroom climate and academic performance. The findings supported the motivational process of study demands-resources (SD-R) model and revealed that perceived classroom climate and student engagement were significant factors linked to academic performance, and practical suggestions were discussed.